Expert consensus statements for Waldeyer's ring involvement in pediatric Hodgkin lymphoma: The staging, evaluation, and response criteria harmonization (SEARCH) for childhood, adolescent, and young adult Hodgkin lymphoma (CAYAHL) group. Issue 9 (16th July 2020) - Seelisch, Jennifer; De Alarcon, Pedro A.; Flerlage, Jamie E.; Hoppe, Bradford S.; Kaste, Sue C.; Kelly, Kara M.; Kurch, Lars; Marks, Lianna J.; Mauz‐Koerholz, Christine; McCarten, Kathleen; Metzger, Monika L.; Stoevesandt, Dietrich; et al.
Abstract: Waldeyer's ring (WR) involvement in pediatric Hodgkin lymphoma (HL) is extremely rare and criteria for determining involvement and response to treatment are unclear. The international Staging, Evaluation, and Response Criteria Harmonization for Childhood, Adolescent and Young Adult Hodgkin Lymphoma (SEARCH for CAYAHL) Group performed a systematic review of the literature in search of involvement or response criteria, or evidence to support specific criteria. Only 166 cases of HL with WR involvement were reported in the literature, 7 of which were pediatric. To date no standardized diagnostic or response assessment criteria are available. Given the paucity of evidence, using a modified Delphi survey technique, expert consensus statements were developed by the SEARCH group to allow for a more consistent definition of disease and response evaluation related to this rare site of involvement among pediatric oncologists. The available evidence and expert consensus statements are summarized.